Does Competition Among Medicare Advantage Plans Matter?: An Empirical Analysis of the Effects of Local Competition in a Regulated Environment - Abe Dunn (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2009)
The regulatory oversight of the private Medicare Advantage (MA) program makes the role of competition in this market unclear. This paper empirically examines the impact of competition by measuring the effects of changes in market structure on enrollment. The study examines competition in local geographic markets using county-level enrollment data from 2001-07. I find that an increase in the number of competitors results in an increase in the number of enrollees served consistent with competition motivating firms to provide more generous benefits. Competition also results in an increase in product proliferation, which highlights a dimension of competition not previously examined. Overall, the results are similar to what one might expect in an unregulated environment, suggesting that there are benefits from competition that are not realized by regulation alone.
Keywords: 330